GnRH therapy in matured Holstein Friesian and Jersey bulls with impaired reproduction - BHASKARAN, R; DUBEY, B MUNILAL (The Indian Journal of Animal Reproduction, 2023)
Effect of GnRH therapy in seven Holstein Friesian (HF) and three Jersey bulls with impaired reproduction aged between4 and 5 years was investigated. The investigated impaired reproductive condition was 'normal libido with very poor quality andquantity of semen'. Each experimental bull received single injection of 20mg of synthetic GnRH (Buserelin-Acetate Receptal®,Hoechst) for 19 consequent times at four days interval, semen was collected in artificial vagina and subjected for detailed analysisof characteristics. GnRH therapy significantly reduced (P
Keywords: GnRH therapy; Taurus bulls; semen characteristics; impaired reproduction